An Efficient SNP System for Mouse Genome Scanning and Elucidating Strain Relationships - Petkov, Petko M.; Ding, Yueming; Cassell, Megan A.; Zhang, Weidong; Wagner, Gunjan; Sargent, Evelyn E.; Asquith, Steven; Crew, Victor; Johnson, Kevin A.; Robinson, Phil; Scott, Valerie E.; Wiles, Michael V.

(untitled) (Genome Research, 2004)
A set of 1638 informative SNP markers easily assayed by the Amplifluor genotyping system were tested in 102 mouse strains, including the majority of the common and wild-derived inbred strains available from The Jackson Laboratory. Selected from publicly available databases, the markers are on average ∼1.5 Mb apart and, whenever possible, represent the rare allele in at least two strains. Amplifluor assays were developed for each marker and performed on two independent DNA samples from each strain. The mean number of polymorphisms between strains was 608±136 SD. Several tests indicate that the markers provide an effective system for performing genome scans and quantitative trait loci analyses in all but the most closely related strains. Additionally, the markers revealed several subtle differences between closely related mouse strains, including the groups of several 129, BALB, C3H, C57, and DBA strains, and a group of wild-derived inbred strains representing several Mus musculus subspecies. Applying a neighbor-joining method to the data, we constructed a mouse strain family tree, which in most cases confirmed existing genealogies.